Pengaplikasian Model Pembelajaran Kooperatif Tipe Teams Games Tournament (TGT) Pada Pembelajaran Besaran dan Satuan di Sekolah Dasar - Nur Aini, Dian; Silmaini Wafa, Aghits; Kurniawati, Wahyu (STAI Denpasar Bali, 2023)
This research aims to increase the activeness and learning outcomes of students in Physics lessons using the Teams Games Tournament type cooperative learning model in class 4 of SD Negeri Tamansari 2 with a total of 24 students. Data was collected using the observation method and a final test in the form of testing Quantity and Unit questions which had been tested for validity, and the level of difficulty using descriptive techniques through percentages and student learning outcomes by calculating the average score and learning completion both individual and classical. The results of data analysis showed that there was an increase in the percentage of student activity in cycle 1 from 65% (quite active) to 85% (very active) in cycle 2. Meanwhile, the learning outcomes of students who achieved completeness increased from cycle 1 by 55%, in cycle 2 by 55%. 88% and student response to the implementation of the TGT type cooperative learning model was 85% (very positive). This research concludes that the use of the cooperative learning model can increase the activity and learning outcomes of grade 4 students at Tamansari 2 State Elementary School